Features of the formation of integration processes of the independent states of Central Asia - Uskembayeva, A.A.; Orazaeva, Zh.Zh. (KSU Publ., 2020)
This article discusses the features of the formation of the integration processes of Central Asian states. The problem of integration of new independent states on the territory of the former Soviet Union into the world community seems extremely urgent for each of them. For the short historical period that has passed since the collapse of the USSR, the new independent states of Central Asia went through a certain stage in their development and revealed some development trends in the economic, political, and cultural fields of these countries. The Central Asian states are united by a lot of historical past, cultural traditions, and religion. All countries have similar circumstances and similar problems. But despite this integration problems, at the moment, are purely technical and economic in nature.
Орталық Азияның тəуелсіз мемлекеттерінің интеграциялық процестерінің қалыптасу ерекшеліктері
Особенности становления интеграционных процессов независимых государств Центральной Азии
Keywords: Central Asia; region; integration; history; unification; culture; independence